AKIBAT HUKUM PENGANGKATAN ANAK BERAGAMA ISLAM TIDAK MELALUI PENETAPAN PENGADILAN AGAMA DI DESA TELUK LATAK KECAMATAN BENGKALIS - Nurul Izzayu; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Adioption of a child is a legal act that diverts a child from the environment of the authority of a parent, legal guardioan or other person who is responsible for the care, education and raising of the child into the foster parent’s family environment. Appointmen of children must be carried out by legal process throught the establishment of a court. So that later child adoption events obtain legal certainty for adopted children and adoptive parents. But the adoption of children that occurred in the village of Teluk Latak Bengkalis district only with agreement of both parties between adoptive parents and biological parents who did not pay attention to the legal consequence that occur after the adoption of children. The problem in this research, namely : first, what are the factors that cause the community in the village of Teluk Latak Bengkalis district to appoint islamic children not through the establishment of the religious court? Second, what is the consequence of the legal ruling on adopting islamic children who do not pass the stipulation of the religious court.This type research can be classified in the type of sosio;ogical research, because the authors directly conduct research on the location or point being examined to provide a complete and clear picture of the problem being examined. This research was conducted in Teluk Latak village Bengkalis district, while the sample population was all parties related to the problem examined in this study, the data source used, primary and secondary data, data collection techniques in this study by interviewing, literature review and analysis data.From the research, there are two things that can be concluded. First, the factors taht cause the community in the village of Teluk Latak Bengkalis district to appoint islamic shildren not through the establishment of the religious court. Second, due to the law on the appoinment of islamic children who do not go through the establishment of the religious court. The writer suggests, there is a need for legal counseling in the village teluk latak about the obligation of adoptive parents to apply for adoption of children in relegious courts.Keywords: Adoption of Children Not Through Court- Teluk Latak Village